What Matters in Cross-Border E-Commerce? A Study of Customer Satisfaction Drivers - Hellena Risvi; Nasar Buntu Laulita (Faculty of Islamic Economics and Business of Universitas Islam Negeri Mataram, 2024)
Purpose: This study aims to identify the variables influencing customer satisfaction in cross-border e-commerce. The variables considered include service quality, information availability, website performance, reliability, security, product variety, price value, delivery, customer service, and personalization.Method: The study employs a quantitative approach, using primary data obtained through a questionnaire survey. Classical assumption tests and multiple linear regression analyses were conducted using SPSS software to evaluate the hypothesized model. A total of 342 validated responses were analyzed, focusing on respondents with experience in cross-border e-commerce transactions.Result: The findings reveal that service quality, security, product variety, price value, and delivery have a significant and positive effect on customer satisfaction. Conversely, information availability, website performance, reliability, customer service, and personalization were found to have no significant impact.Practical Implications for Economic Growth and Development: This research offers valuable insights for cross-border e-commerce businesses to enhance the key drivers of customer satisfaction. Improving these factors can increase customer retention and loyalty, leading to higher repeat purchases and trust in the platforms, thereby boosting sales and revenue. By attracting a larger international customer base and expanding market share, businesses can achieve a competitive advantage in the global marketplace. This contributes to the promotion of international trade and fosters economic integration.